Police Cybercrime Training: Perceptions, Pedagogy, and Policy. (26th October 2018) - Cockcroft, Tom; Shan-A-Khuda, Mohammad; Schreuders, Z Cliffe; Trevorrow, Pip
Abstract: Cybercrime presents numerous issues for police organizations. A key challenge is to understand how best to impart relevant skills and knowledge about cybercrime throughout the organization to enable police officers to react appropriately to such incidents. This article is drawn from research undertaken as part of the CARI Project, a major study into the effectiveness of cybercrime investigation within a large UK police force funded by the Police Knowledge Fund. As part of the needs assessment for the above project, concerns were raised about the effectiveness of existing training arrangements in facilitating the development of cyber skills within police officers. The present research, based on survey data, explored the effectiveness of different training styles as perceived by those who had undertaken cyber training. The research found that officers perceived some modes of training as more effective than others and highlighted some of the organizational contexts that impact negatively on the delivery of effective cyber training. The findings are presented within a context, informed by existing literature, that acknowledges wider debates surrounding the pedagogy of police learning and the organizational challenges of developing cyber skills within police officers. The authors believe that the findings will have relevance to police training policy both in the UK and in the wider international context.